ENDOMETRIOSIS: THE IMPORTANCE OF EARLY IDENTIFICATION AND NURSING FOLLOW-UP - de Sousa Santos , Elidiomar (Health and Society, 2023)
This work is intended to guide and show the importance of early diagnosis of Endometriosis and the importance of nursing participation, presenting the risks of late diagnosis and the main causes that lead to the impossibility of treatment without sequelae. Identify the importance of the signs and symptoms that endometriosis presents and that many women are confused due to the lack of essential information for a better quality of life. Showing that nursing can contribute and help a lot to identify and discern the symptoms between what is the pain of a menstrual cramp and the pain of a cramp in someone who has endometriosis.